Molecular diagnostics in periodontics – A review - Divya Shree .P,; Priyanka K Cholan,; Dhayanad John Victor,; Sumi Priyadarshini .S, (International Journal of Pharma and Bio Sciences, 2020)
Although over 700 bacterial species make up the oral flora, it is thought that only a handful of species contribute to the initiation and progression of periodontitis. For over 20 years, culture and microscopy techniques have been the primary method of identifying and studying putative pathogens. The very fact that each organism has a unique 16s rRNA sequence is the basis for the evolution of the Molecular Science Approximately 35% of the oral bacterial species have not yet been cultured in vitro. The drawbacks of these various techniques have unraveled the scope of molecular diagnostic techniques in periodontal diagnostics. With the application of these methods significant improvements have been made in the field of periodontal diagnostics. These tests are based on the identification of the inflammatory mediators, decomposed tissue products or detection of bacteria or its antigens. Herein our focus is to describe these DNA based, culture independent methods for their use or potential use in molecular microbial diagnosis and particularly highlight the methods that are prominent in the field of Periodontics.